Improvement Scheme and Static Strength Analysis Based on Existing Metro Pantograph - Jiejun LYU (机车电传动)
For a long time, the problems such as structural parts cracking, failure of structural parts, pantograph and network accidents, and abnormal wear of the skate were revealed in the application of the subway pantograph in China. In order to improve the reliability, stability and service life of metro pantograph, the metro pantograph was improved to adapt to the stringent domestic rigid catenary lines. The analysis and verification showed that the improved scheme was reliable and has been applied in Shenzhen, Nanjing and other metro stations.